2020
DOI: 10.1177/0363546520962774
|View full text |Cite
|
Sign up to set email alerts
|

Application of Autogenous Urine-Derived Stem Cell Sheet Enhances Rotator Cuff Healing in a Canine Model

Abstract: Background: A repaired rotator cuff (RC) often heals with interposed scar tissue, making repairs prone to failure. Urine-derived stem cells (USCs), with robust proliferation ability and multilineage differentiation, can be isolated from urine, avoiding invasive and painful surgical procedures for harvesting the cells. These advantages make it a novel cell source for autologous transplantation to enhance RC healing. Hypothesis: Implantation of an autogenous USC sheet to the injury site will enhance RC healing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 66 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…Sun, Y [ 125 ] demonstrated that the bone-tendon composite autograft group had a higher tendon maturity score than simple suture. Chen, Y [ 126 ] discussed the stem cell sheets derived from urine of the patient, and the comparison with the tendon-bone suture showed that the cell sheet group presented more collagen fibers at the tendon-bone interface. Sener, M [ 127 ] compared the results between patellar tendon-bone autograft with free flexor tendon autograft, and found that the patellar tendon-bone autograft was completely integrated with the tibia.…”
Section: Resultsmentioning
confidence: 99%
“…Sun, Y [ 125 ] demonstrated that the bone-tendon composite autograft group had a higher tendon maturity score than simple suture. Chen, Y [ 126 ] discussed the stem cell sheets derived from urine of the patient, and the comparison with the tendon-bone suture showed that the cell sheet group presented more collagen fibers at the tendon-bone interface. Sener, M [ 127 ] compared the results between patellar tendon-bone autograft with free flexor tendon autograft, and found that the patellar tendon-bone autograft was completely integrated with the tibia.…”
Section: Resultsmentioning
confidence: 99%
“…12,44 The multilineage differentiation potential of the expanded IPFP MSCs toward bone, cartilage, and fat was characterized, and the positive induction of osteogenesis, chondrogenesis, and adipogenesis was determined using alkaline phosphatase staining, safranin O staining, and oil red O staining, respectively. 6,7,13 Isolation and Identification of IPFP MSC-Derived Exosomes (IMEs) Exosome isolation from IPFP MSCs was conducted in accordance with a previously described protocol. 54,58 When the IPFP MSCs reached 70% to 80% confluency on a 10-cm dish (EasYDish; Thermo Fisher Scientific), the cells (~10 6 /10-cm dish) were washed twice using PBS, and the medium was replaced by medium containing exosome-depleted fetal bovine serum (Invitrogen).…”
Section: Culture and Characterization Of Ipfp Mscsmentioning
confidence: 99%
“…As progenitor cells derived from the urinary system, the USCs can be isolated readily from urine and expand extensively through culturing [ 54 ]. Such cells possess the desired regenerative properties including robust proliferative capacity [ 55 ], multipotential for differentiation [ [56] , [57] , [58] , [59] , [60] ], paracrine effect [ [61] , [62] , [63] ], and immune-modulatory property [ 29 ], and have been tested in animal models for a multitude of human diseases [ 29 , [64] , [65] , [66] , [67] , [68] ]. Previous studies have also demonstrated that the USCs could differentiate into multiple bladder cell lineages identifiable by particular gene and/or protein markers, and provide an ideal cell source for the reconstruction of urinary tract [ 12 , 57 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%